Paintable liquid-crystal displays. - Hellemans, A.
A new technology may make LCDs as ubiquitous as printed paper.
Keywords: UV induced polymerization; Enforced stratification; Isobornylmethacrylate; Paintable liquid-crystal displays; Stilbenedimethacrylate; Top sealing layer